(untitled) (Journal of Institute of Science and Technology, 2017)
This study was focused on Macaca assamensis general behavior and vegetation associated with their habitats in Kaligandaki River Basin at Baglung and Parbat Districts of Nepal. The field survey was conducted from December, 2015 to May, 2016 to explore the Assamese Macaque general behavior and vegetation associated with their habitats. Total area of 104.70 km2 was surveyed, vegetation analysis was done by random quadrates sampling method and behavioral data were collected by scan sampling method. A total of 47 individuals of Assamese Macaques (Macaca assamensis) were counted in four different troops. Total of 2240 scan samples were recorded from the four different troops during this study period the scan samples revealed that foraging was 47%, moving 28%, resting 14% and grooming 11%. In the context of daily activity pattern for aging time of Assamese monkey was found to be highest 54% in 15:00 to 18:00 observational phase and lowest 40% in the observational phase of 12.00 to 15.00 hours. Moving time of the Assamese monkey was found to be highest 33% in 12.00 to 15.00 observational phase and lowest 22% at 15:00 to 18:00 observational phase, resting time of Assamese monkey was found to be highest 15% in 09:00 to 12:00 hours and lowest 13% in 15:00 to 18:00 observational phase and Assamese monkey were seen mostly grooming 13% in 12.00 to 15.00 hours and lowest 10% in 15:00 to 18:00 observational phase. By quadrate sampling, 58 plant species with 716 number were recorded. Sal (Sorea robusta) was the dominant plant species with relative density 31.42% and relative frequency 8.376% which was followed by Tiju (Diospyros malabarica)with relative density 10.93% and relative frequency 8.376%. Journal of Institute of Science and Technology Volume 22, Issue 1, July 2017, page: 110-119